Association of the COVID-19 pandemic with bystander cardiopulmonary resuscitation for out-of-hospital cardiac arrest: a population-based analysis in Tokyo, Japan. Issue 8 (15th June 2022) - Shibahashi, Keita; Kawabata, Hiromitsu; Sugiyama, Kazuhiro; Hamabe, Yuichi
Abstract : Background: The impact of the COVID-19 pandemic on bystander cardiopulmonary resuscitation (CPR) for out-of-hospital cardiac arrest (OHCA) is unclear. This study aimed to investigate whether rates of bystander CPR and patient outcomes changed during the initial state of emergency declared in Tokyo for the COVID-19 pandemic. Methods: This retrospective study used data from a population-based database of OHCA maintained by the Tokyo Fire Department. By comparing data from the periods before (18 February to 6 April 2020) and during the declaration of a state of emergency (7 April 2020 to 25 May 2020), we estimated the change in bystander CPR rate, prehospital return of spontaneous circulation, and survival and neurological outcomes 1 month after OHCA, accounting for outcome trends in 2019. We performed a multivariate regression analysis to evaluate the potential mechanisms for associations between the state of emergency and these outcomes. Results: The witnessed arrest rates before and after the declaration periods in 2020 were 42.5% and 45.1%, respectively, compared with 44.1% and 44.7% in the respective corresponding periods in 2019. The difference between the two periods in 2020 was not statistically significant when the trend in 2019 was considered. The bystander CPR rates before and after the declaration periods significantly increased from 34.4% to 43.9% in 2020, an 8.3% increase after adjusting for the trend in 2019. This finding was significant even after adjusting for patient and bystander characteristics and the emergency medical service response. There were no significant differences between the two periods in the other study outcomes. Conclusion: The COVID-19 pandemic was associated with an improvement in the bystander CPR rate in Tokyo, while patient outcomes were maintained. Pandemic-related changes in patient and bystander characteristics do not fully explain the underlying mechanism; there may be other mechanisms through which the community response to public emergency increased during the pandemic.